Matbaalar ve reklam ajansları arasındaki teknik problemlerin tespiti ve çözüm önerileri - Mutafoglu, İbrahim Cemal (My University, 2013)
MATBAALAR VE REKLAM AJANSLARI ARASINDAKİ TEKNİK PROBLEMLERİN TESPİTİ VE ÇÖZÜM ÖNERİLERİ Matbaalar; gazete, kitap, dergi, broşür, ambalaj vb. gibi basılı materyalleri, uygun baskı tekniği kullanarak üretme ve çoğaltma görevini üstlenmiş kuruluşlardır. Reklam ajansları ise fiziki üretimden çok, resmi ve özel kuruluşların hizmet ya da mallarını tanıtmaya, sevdirmeye, sattırmaya yönelik alternatif düşünceler üreten, reklam/ tanıtım kampanyalarını organize eden ve basılacak materyallerin baskı öncesi hazırlık işlemlerini gerçekleştiren kuruluşlardır. Matbaalar ve reklam ajansları arasında yaşanan teknik problemler, reklam ajanslarının istedikleri özelliklerde kaliteli ürünleri elde edememelerine, matbaaların ise gerek işgücü gerekse zaman bakımından kayıplar yaşamasına neden olmaktadır. Bu aşamada da matbaalar ve reklam ajansları arasında anlaşmazlıklar çıkmaktadır. Yapılan bu çalışma ile bu anlaşmazlıkların kaynağı olan teknik problemleri tespit ederek çözümlerine yönelik öneriler sunmak hedeflenmiştir. Böylelikle yaşanılan anlaşmazlıkların minimuma indirgenmeleri amaçlanmıştır. Bu amaçla öncelikle, matbaalar ve reklam ajanslarında ön değerlendirmeler yapılmış ve elde edilen bulgular neticesinde, matbaalar ve reklam ajansları için iki ayrı anket oluşturulmuş ve uygulanmıştır. Reklam ajanslarına uygulanan ankette; kullandıkları masaüstü yayıncılık programları, dosya kayıt formatları, işin matbaadaki baskı sistemine uygun olarak hazırlanması, işe uygun kâğıt seçimi, cilt şeklinin detaylandırılması, ozalit, renk provası alınması, baskı provası alınması, onay sürecinde karşılaşılan problemler ve yaşanılan diğer teknik sorunlarla ilgili detaylar sorulmuştur. Matbaalara uygulanan ankette ise; aynı konularda matbaa çalışanlarının bilgi düzeyi incelenmiş, sonuçta çözüm önerilerinin elde edilebileceği; reklam ajanslarıyla iş akışını sağlayan birimler ve teknik konulardaki sorunlarla ilgili detaylar sorulmuştur. Bu ve benzeri sorunların çözümü ile ilgili olarak uygulanan anketten elde edilen sayısal verilerin SPSS analizi çıkarılmıştır. Elde edilen sonuçlarla matbaalar ve reklam ajanslarının üretim sürecinde yaşadıkları teknik problemlerin neler olduğu ve nasıl önüne geçilebileceği ile ilgili önerilerde bulunulmuştur.

DETECTION OF TECHNICAL PROBLEMS BETWEEN PRINTING HOUSES AND ADVERTISING AGENCIES, AND SUGGESTIONS FOR SOLUTIONS Printing houses are organizations that undertake the task of producing and replicating printed materials such as newspapers, books, magazines, brochures, packaging, etc. using appropriate print techniques. Advertising agencies, on the other hand, are establishments that generate alternative ideas in order to promote, ingratiate, and sell the goods or services of public or private organizations, organize advertising/ promotional campaigns, and perform pre-press of the materials to be printed rather than doing physical production. Technical problems experienced between printing houses and advertising agencies lead advertising agencies’ not achieving quality products with desired properties as well as resulting losses in terms of time and labour on the side of printing houses. At this stage, disagreements between them occur. In this study, the purpose is to provide recommendations for solutions by identifying technical problems leading to these disputes. Thus, conflicts experienced are aimed to be reduced to an optimum level. To realize these aims, first, preliminary assessments in printing houses and advertising agencies have been made, and then, as the result of the assessments made, two separate surveys for printing houses and advertising agencies have been generated and applied. To this end, firstly, preliminary assessments in printing houses and advertising agencies have been done, and as the result of the evaluations obtained from them, two separate surveys for printing houses and advertising agencies have been prepared and applied. In the survey applied to advertising agencies, details about desktop publishing programs and file record formats they use, preparation of the work in accordance with the printing system in the publishing house, selection of the appropriate paper type, detailing the shape of the skin, blueprints, colour rehearsal, problems encountered during the approval process, and other technical problems experienced have been asked. In the survey of printing houses, details that will respond to the questions asked to the advertising agencies and will help to obtain possible solutions have been inquired as well as asking the details about units providing workflow with advertising agencies and problems in technical issues. The numeric data obtained from the questionnaire that was applied concerning the solutions of these problems and alike were analysed using SPSS software. With the results attained, the kind of technical problems printing houses and advertising agencies have in the production process have been detected and suggestions about how to avoid these problems have been proposed.
Keywords: Matbaa Eğitimi; Reklam